Kinetika dan mekanisme sistem transpor Cd(II) antar fasa melalui teknik membran cair fasa ruah dengan oksin sebagai zat pembawa - Kahar, Zaharasmi; Mustafa, Djufri; -, Wiwit (Jurnal Riset Kimia, 2007)
ABSTRACT The transport and separation of Cd(II) through  bulk liquid membrane technique had been investigated and optimised. Cd(II) was transported  through a liquid membrane  of  chloroform solution containing oxine as mobile carrier and  received by EDTA in stripping phase. In compliance with optimum condition, the flux of Cd(II) crossing the membrane was studied, and applied further into a model of the transport system and kinetics mechanism. Concentration of Cd(II) in feed  and stripping phases were experimentally determined, and monitored by the atomic absorption spectrophotometer at lmaks 228.8 nm.  The model curve of time dependence of Cd(II) reduced concentrations in the feed, membrane and  stripping phases show good agreement and characterized as a transport system for Cd(II) interphase involved two consecutive irreversible first order reactions. The rate constant of transport at temperature 28°C are k1 0.0416 minutes-1, k2 0.0354  minutes-1 and  activation energy  32.96 kJ mol-1